Analysis Of The Use Of Sarcasm Language Style In Student Interactions - Ririn Rahayu (Jurnal Serambi Ilmu, 2023)
The purpose of this study is to describe the types of sarcasm and stylistic elements used by MTsN 2 Aceh Utara students in interacting with each other. This research is based on a descriptive qualitative methodology. The information for this survey comes in the form of sarcastic words, phrases and sentences that MTsN 2 Aceh Utara students use in their interactions. The students of MTsN 2 Aceh Utara in grades VII, VIII, and IX served as the study's data source. This study included note-taking, recording, and listening techniques to obtain data. Based on the research’s findings, it was discovered that students of MTsN 2 Aceh Utara used sarcasm in the form of 43 data that could be grouped into four categories: (a) speaking with bitterness of 10 data, (b) bitter reproach of 8 data, (c) biting lips in anger with no data found, and (d) mocking or scathing satire of 26 data. 43 data point to factors that have an impact on MTsN 2 Aceh Utara students' use of sarcasm. Factors that influence the use of sarcasm style in MTsN 2 Aceh Utara students are as many as 43 data. This data can be described in detail, (a) 15 data of peer influence, (b) 5 data of emotional factors, (c) 15 data of weak knowledge of language, and (d) 8 data of the influence of television and film media. This data can be broken down into the following categories: (a) 15 data on peer influence; (b) 5 data on emotional aspects; (c) 15 data on language proficiency; and (d) 8 data on the impact of television and films.